Correlação entre a estabilidade termodinâmica e o comportamento reológico em materiais microemulsionados - Cotrim, Aron Carlos de Melo (2015)
New delivery systems that enable the delivery of drugs and other molecules has been explored recently. Among them, the microemulsion materials has met the expectations related to compartmentalization, improvement of dissolution and biocompatibility standards. The characterization of the thermodynamic stability of these materials has been a limiting factor in their application. Because these materials fluids understanding the rheological profile can be directly associated with the thermodynamic stability of microstructures. This study sought to determine and correlate the thermodynamic stability and the rheological behavior of some samples of microemulsion materials. Pseudoternários diagrams were prepared using Span 80 (SP), Tween 80 (TW), 1-butanol (BT), distilled water and triglyceride of capric / caprylic acid. The ME regions were delimited in pseudoternário diagram and points were pre-selected. Rheological characterization was performed. The samples were subjected to a preliminary stability test, by evaluating pH, conductivity, physical appearance and maintenance of rheological characteristics. The results of stability tests were correlated rheological analysis by determining the Pearson correlation coefficient. All samples diagram SP/TW/BT (3.5/5.5/1.0) were approved after centrifugation, except 15M, 16M, 17M and 18M. The amostras1M, 2M, 3M, 4M, 5M, 6M, 7M, 8M, 9M, 11M, 12M and 13M, no significant change in the value of the hysteresis area, and kept the Newtonian classification, and also adopted in all tests physical and chemical stability. Samples 10M, 14M, 15M, 16M, 17M and 18M presented rheological and stability changes, classificas being as non-Newtonian and unstable. The pH and electrical conductivity analysis showed a direct correlation with respect to hysteresis area. The flow curves showed Newtonian behavior with the hysteresis area between +0.20 e - 0.20Pa/s is indicative of thermodynamically stable system MEs The study of the rheological behavior is an important tool decrease analysis time during the development of new materials. The Pearson correlation coefficient demonstrated that there is a correlation between the rheological behavior ea thermodynamic stability analyzes in order que one rheology can be incorporated TO Stability testicles thermodynamics paragraph MEs .